Evaluation of the clinical and demographic data of patients requiring revision after lumbar spinal stenosis surger - Karaali, Evren; Ciloglu, Osman (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the clinical and demographic data of patients requiring revision surgery after lumbar spinal stenosis (LSS) surgery and to provide a guide us in choosing primary surgical options.Material and Methods: This study was conducted as a single-center, descriptive, and retrospective study. LSS patients, who were operated upon using the same implant technique between 2012 and 2017, and subsequently underwent revision surgery due to implant failure and operated by the same surgeon were included. Medical records, preoperative and postoperative two-plan radiographs, and computed tomography (CT) scans of the primary and revision surgeries of the patients were evaluated.Results: A total of 19 patients (5 males, 14 females) with a mean age of 64.16 ± 7.9 years (range: 47 to 77 years) were included in the study. Most of the patients who underwent revision surgery were over 65 years of age and had a normal body mass index (BMI). In addition, 16 patients (84.2%) who underwent revision surgery were operated without transforaminal lumbar inter-body fusion (non-TLIF). L5-S1 was the most commonly seen level for spinal stenosis revision. The mean revision time was 245.26 ± 65.1 days (range: 135 to 342).Conclusion: Debates are ongoing between transforaminal lumbar inter-body fusion (TLIF) and non-TLIF surgery. In light of the data obtained through this study, we think that TLIF cage surgery should be included in the primary surgical procedure, especially at the lumbosacral junction, where it is difficult to obtain fusion to avoid revision in patients undergoing LSS surgery.
Keywords: Lumbar spinal stenosis; transforaminal lumbar inter-body fusion; revision